Answer:
9/4 or 2 1/4.
Step-by-step explanation:
3/4 / 1/3
=3/4 * 3/1
= 9/4
Answer:
3/4 ÷ 1/3 equals
(3/4 x 3/1) = 9/4
Step-by-step explanation:
Find the sixth term of the
geometric sequence, given the
first term and common ratio.
a1=5 and r=3/2
Answer:
[tex]\frac{1215}{32}[/tex]
Step-by-step explanation:
The n th term of a geometric sequence is
[tex]a_{n}[/tex] = a₁ [tex](r)^{n-1}[/tex], hence
[tex]a_{6}[/tex] = 5 × [tex](\frac{3}{2 )} ^{5}[/tex] = 5 × [tex]\frac{243}{32}[/tex] = [tex]\frac{1215}{32}[/tex]
The sixth term of the geometric sequence is 1215/32 given that the first term a₁=5 and common ratio r=3/2. This can be obtained by using formula for nth term of the geometric sequence.
What is a geometric sequence?
Sequence is s collection of objects in a particular order and repetitions are allowed.
Geometric Sequence:
a, ar, ar¹, ..., arⁿ⁻¹ is a geometric sequence, where a is the first term, r is the common ratio and arⁿ⁻¹ is the nth term.
Calculate the sixth term:From the definition, nth term of a geometric sequence is arⁿ⁻¹.
Given that, a₁=5 and r=3/2
To find sixth term, put n=6 ⇒ arⁿ⁻¹=(5)(3/2)⁶⁻¹
=(5)(3/2)⁵
=5(3⁵/2⁵)
=5×(243/32)
=1215/32
Hence the sixth term of the geometric sequence is 1215/32 given that the first term a₁=5 and common ratio r=3/2.
Learn more about geometric sequence here:
brainly.com/question/2959141
#SPJ2
In the table, the parts of strawberry concentrate and the parts of water to prepare a strawberry drink are given. There is a proportional relationship between these two quantities. Find the value of x.
Parts of Water 3 9 36
Parts of Concentrate 1 3 x
Answer:
12
Step-by-step explanation:
[tex]\frac{Parts of Water}{Parts of Concentrate} =3[/tex]
3/1=3
9/3=3
36/12=3
what is the coefficient of x^3 in the expansion of (2x-3)^5?
A) -5
B) 10
C) -120
D) -360
E) 720
Answer:
309
Step-by-step explanation:
(2x-)^5
step 1
1 5 10 10 5 1
step 2
1(2x¹-3^0) 5(2x²-3^5) 10(2x³-3^4)
10(2x^4-3³) 5(2x^5-3²)
1(2x^0-3¹)
step 3
(2x) (10x²-243) (20x³-81) (20x^4-27)
(10x^5-9) (2-3)
step 4
2 -243-61-7 +1 -1=309
The coefficient of [tex]x^3[/tex] in the expansion of [tex](2x-3)^5[/tex] is 720
The correct answer is an option (E)
What is coefficient?"It refers to a number or quantity placed with a variable."
What is variable?"The alphabetic character that expresses a numerical value."
What is an expression?"It is a mathematical expression which consists of numbers, variables and mathematical operations."
Formula for [tex](a-b)^3[/tex]" [tex](a-b)^3=a^3-3a^2b+3ab^2- b^3[/tex] "
Formula for [tex](a-b)^2[/tex]" [tex](a-b)^2=a^2-2ab+b^2[/tex] "
For given question,
We have been given an expression [tex](2x-3)^5[/tex]
We need to expand given expression.
[tex](2x-3)^5\\\\= (2x-3)^3\times (2x-3)^2\\\\=[(2x)^3-3(2x)^23+3(2x)(3)^2- 3^3]\times ((2x)^2-2(2x)(3)+3^2)\\\\=[8x^3-36x^2+54x-27]\times [4x^2-12x+9]\\\\=-243+810x-1080x^2 +720x^3-240x^4+32x^5\\\\=32x^5-240x^4+720x^3-1080x^2+810x-243[/tex]
Therefore, the coefficient of [tex]x^3[/tex] in the expansion of [tex](2x-3)^5[/tex] is 720
The correct answer is an option (E)
Learn more about the coefficient here:
https://brainly.com/question/13431100
#SPJ2
Solve.
{y=x−82x+3y=1
Use the substitution method.
(5, −3)
(4, −4)
(0, −8)
(2, −6)
Answer:
(5,-3) if the system is
y=x-8
2x+3y=1
Step-by-step explanation:
I think the system is to read:
y=x-8
2x+3y=1.
Please correct me if I'm wrong.
I'm going to plug 1st equation into 2nd equation giving me:
2x+3(x-8)=1 ->I replaced y with (x-8).
Distribute:
2x+3x-24=1
Combine like terms:
5x-24=1
Add 24 on both sides:
5x=25
Divide both sides by 5:
x=5
If y=x-8 and x=5, then y=5-8=-3.
The solution is (5,-3).
(5, −3) is the solution of given system of equations.
What is equation?"It is a mathematical statement which consists of equal symbol between two algebraic expressions."
What is a system of equations?"It is set of equations for which we find a common solution."
What is substitution method?"It is a method of solving system of equation we substitute the value of a variable found by one equation in the second equation."
For given question,
We have been given a system of equations.
y = x - 8 ..............(i)
2x + 3y = 1 ...............(ii)
We use substitution method to solve given system of equations.
Substitute the value of y from (i) to equation (ii).
⇒ x + 3(x - 8) = 1
⇒ 2x + 3x - 24 = 1
⇒ 5x = 1 + 24
⇒ 5x = 25
⇒ x = 5
Substitute above value of x in an equation (i)
⇒ y = 5 - 8
⇒ y = -3
So, the solution of given system of equations is x = 5 and y = -3
Therefore (5, -3) is the solution of given system of equations.
Learn more about the substitution method here:
https://brainly.com/question/14619835
#SPJ2
point O is the center of this circle. What is the m<CAB
A). 55°
B). 48°
C). 45°
D). 35°
Answer:
B
Step-by-step explanation:
The angle on the circumference is half the angle subtended at the centre by the arc CB, that is
∠CAB = 0.5 × ∠COB = 0.5 × 96° = 48° → B
m∠CAB is 48° given that point O is the center of the circle and ∠COB is 96°. This can be obtained by using the circle theorem.
What is circle theorem ?Circle Theorem: The angle subtended by an arc at the center is double the angle subtended by it at any point on the remaining part of the circle.Given that, ∠COB = 96°
By applying Circle theorem, we can say that
∠COB = 2∠CAB
96° = 2∠CAB
∠CAB = 96°/2 = 48°
∠CAB = 48°
Hence m∠CAB is 48° given that point O is the center of the circle and ∠COB is 96°.
Learn more about circle theorem here:
brainly.com/question/17158173
#SPJ2
What is the equation of the line that is parallel to the given line and passes through the point (-3, 2)?
4x + 3y = -6
Step-by-step explanation:
evaluate 3^-3 please explain
Answer:
D) 1/27
Step-by-step explanation:
The question is: 3^(-3).
Note that there is a negative sign in the number at the power place. This means that you must flip the number, and in this case, put it over 1. The rest is solved as usual:
3^-3 = 1/(3^3) = 1/(3 * 3 * 3) = 1/27
1/27, or D) is your answer.
~
use elimination method to solve the system of equations. Choose the correct order pair. -x+5y=-4 4x+4y=16
Answer:
(4,0)
Step-by-step explanation:
So we have the system:
-x+5y=-4
4x+4y=16
--------------
We are asked to solve this for elimination.
We aren't totally setup for elimination though.
Both equations are in the same form, the form being ax+by=c form, so we are good there.
Now the other requirement is one the columns that contain variables need to be opposites (you will add) or same (you will subtract).
I'm going to multiply the first equation by 4. The reason I'm going to do this is because the first column will contain -4x and 4x. Those are opposites. When you add opposites, you get 0 (they cancel).
So applying the multiplication of 4 to first equation gives:
-4x+20y=-16
4x+ 4y=16
----------------- Add the equations now.
0x+24y=0 Again this is called elimination, because we made it to where a variable is canceled when combining the equations.
0x+24y=0
0+ 24y=0
24y=0
Divide both sides by 24:
y=0
So using one of the equations (you only need one of them) along with the y=0, let's find x.
I'm going to go with -x+5y=-4 with y=0.
Plugging in the 0 for y gives us:
-x+5y =-4
-x+5(0)=-4
-x+ 0 =-4
-x =-4
Multiply both sides by -1:
x =4
The solution is (x,y)=(4,0).
ANSWER
The ordered pair is
(4,0)
EXPLANATION
To solve a simultaneous equation using the elimination method means making the coefficient of one of the variables the same. We then add or subtract to eliminate that variable.
The given system has equations:
[tex] - x + 5y = - 4...(1)[/tex]
[tex]4x + 4y = 16...(2)[/tex]
Divide the second equation by 4
[tex]x + y = 4...(3)[/tex]
Add equation (1) and (3) to eliminate x.
[tex] \implies \: 5y + y = - 4 + 4[/tex]
[tex] \implies \: 6y = 0[/tex]
[tex] \implies \: y = \frac{0}{6} = 0[/tex]
Put
[tex]y = 0[/tex]
into the first equation to get:
[tex] - x + 5 \times 0 = - 4[/tex]
[tex] - x = - 4[/tex]
[tex] \therefore \: x = 4[/tex]
The ordered pair is
(4,0)
What is the missing term?
(10х — 4х2) - (7х + ?) = 3х – 6х2
(10х — 4х2) - (7х + ?) = 3х – 6х2
10x - 7x = 3x which is given,
Now you have -4x^2 - ? needs to equal -6x^2
write it as an equation:
-4x^2 - ? = -6x^2
To solve for ? add 4x^2 to each side:
-? = -2x^2
Multiply each side by -1:
? = 2x^2
Which equation is used to help form the combined gas law?
Need help ASAP !
If pressure is constant
then PV= nRT
is equivalent to V= ( nR/P) T
V= kT ( where k is constant nR/P)
As V is directly proportional to T
So V1/T1 = V2/T2
Answer:
The correct answer
Step-by-step explanation:
Which of the following is equivalent to
Answer:
[tex]x^{4}[/tex]
Step-by-step explanation:
[tex]\frac{x^{5}y^{2} }{xy^{2} }[/tex]
= [tex]x^{4}[/tex]
Question 1:
For this case we have the following expression:
[tex]\frac {x ^ 5y ^ 2} {xy ^ 2}[/tex]
We eliminate similar terms in the numerator and denominator:
[tex]\frac {x ^ 5} {x}[/tex]
By definition of division of powers of the same base we have to place the same base and subtract the exponents:
[tex]\frac {x ^ 5} {x} = x ^ {5-1} = x ^ 4[/tex]
ANswer:
Option D
Question 2:
For this case we must indicate which expression is not equal to 125.
We tested option A:
[tex]5 (\frac {5 ^ 3} {\frac {2} {5}}) ^ 2 =[/tex]
Simplifying we have:
[tex]5 (\frac {5 ^ 3 * 5} {2}) ^ 2 =\\5 (\frac {5 ^ 8} {4}) =\\\frac {5 ^ 9} {4}[/tex]
The expression is not equal to 125.
Answer:
option A
Arnold has x amount of money in
his checking account. He spends
$12.36 for breakfast but has at least
$31.24 left in his account. How much
money did he have originally?
Answer:
43.60
Step-by-step explanation:
12.36+31.24
what is 6/7divided into 3/14 plz helppp meh
Answer:
4
Step-by-step explanation:
6/7 divided by 3/14 is 4.
Find common denominators.
6/7 would be changed into 12/14.
3/14 would stay the same because its denominator is already 14.
12/3 = 4
Therefore, 6/7 divided by 3/14 is 4.
Answer:
The answer is 4
Step number one use the butterfly method:
6 14
-- ×---- =84/21
7 3
Step 2: Divide since it's improper
84÷21=4
4 21
-- × --- =4
1 21
Find one positive and one negative angle coterminal with an angle of [tex]\frac{11pi}{8}[/tex].
idk how to do the pi sign
Answer:
see explanation
Step-by-step explanation:
Co terminal angles are angle ± 2π, that is
[tex]\frac{11\pi }{8}[/tex] + 2π
= [tex]\frac{11\pi }{8}[/tex] + [tex]\frac{16\pi }{8}[/tex] = [tex]\frac{27\pi }{8}[/tex]
and
[tex]\frac{11\pi }{8}[/tex] - 2π
= [tex]\frac{11\pi }{8}[/tex] - [tex]\frac{16\pi }{8}[/tex] = - [tex]\frac{5\pi }{8}[/tex]
(3a-2b)(3a+3b) so this is foil but i always get messed up on it does anyone now how to do it
Answer:
9a^2 + 3ab - 6b^2
Step-by-step explanation:
(3a-2b)(3a+3b)
First term of each grouping is 3a and 3a.
Multiply those you get 9a^2.
Outer term of each grouping is 3a and 3b.
Multiply those you get 9ab.
Inner term of each grouping is -2b and 3a.
Multiply those you get -6ab.
Last term of each grouping is -2b and 3b.
Multiply those you get -6b^2.
Add up all your products from above.
9a^2+9ab+-6ab+-6b^2
There are like terms here. The 9ab+-6ab which is 3ab.
So you can write your expression now as:
9a^2 + 3ab +-6b^2
9a^2 + 3ab - 6b^2
Step-by-step explanation:
[tex]\text{Use FOIL}\ (a+b)(c+d)=ac+ad+bc+bd:\\\\(3a-2b)(3a+3b)\\\\=(3a)(3a)+(3a)(3b)+(-2b)(3a)+(-2b)(3b)\\\\=9a^2+9ab-6ab-6b^2\qquad\text{combine like terms}\\\\=9a^2+3ab-6b^2[/tex]
find the value of x
An outside angle is equal to the sum of the two opposite inside angles.
The triangle has an outside angle of 98, it's two opposite inside angles are given as 32 and X.
To find X, subtract 32 from 98.
X = 98 - 32 = 66
The answer is B.
Question 1
1 pts
Maureen worked 48 hours last week. Her hourly rate is $8.00. What was her salary, not
including overtime pay?
• 384.00
230.00
320.00
480.00
Answer:
$384.00
Step-by-step explanation:
Since $8..0 is 1 hour, just multiply 48 x 8! Hope this helps!
Answer:
320
Step-by-step explanation:
The reason that you 48* 8 is because the 48 has overtime included in it so you would only 40*8.
what is the approximate area of the circle shown below? 16 cm
Answer:
201.143 (approx.) cm²
area of circle = (pi)x(radius)^2
= 22/7 x (8)^2
=22/7 x 64
= 1408/7
= 201.142857143
= 201.143 cm^2 (approx.)
Answer:
the approximate area of circle is 201 cm²
D is the correct option.
Step-by-step explanation:
From, the given figure, the diameter of the circle is 16 cm.
The radius is half of the diameter.
Hence, the radius of circle is 16/2 = 8 cm
The area of a circle is given by
[tex]A=\pi r^2[/tex]
Substituting the value of r and π
[tex]A=3.14(8)^2\\\\A=200.96\\\\A\approx201[/tex]
Therefore, the approximate area of circle is 201 cm²
D is the correct option.
Given the functions, F (x)=√(2x-5) and g(x) = 3x 2 + 2, perform the indicated operation. f(g(x))
Answer:
[tex]f(g(x)) =\sqrt{6x^2-1}[/tex]
Step-by-step explanation:
Given
f(x) = √2x-5
and
g(x) = 3x^2+2
We have to find the composition of both function
f(g(x)) means that we have to put function g in place of x in function f.
[tex]f(g(x))= \sqrt{2*g(x)-5}\\ =\sqrt{2(3x^2+2)-5}\\=\sqrt{6x^2+4-5}\\=\sqrt{6x^2-1}[/tex]
..
The composite function f(g(x)) is given by f(g(x)) = √(6x^2 - 1).
To find the composite function f(g(x)), you need to substitute the expression for g(x) into the function f(x). Here's how you can do it step by step:
Start with the function g(x):
g(x) = 3x^2 + 2
Now, substitute this expression into the function f(x):
f(g(x)) = √(2(3x^2 + 2) - 5)
Simplify the expression inside the square root:
f(g(x)) = √(6x^2 + 4 - 5)
Further simplify the expression inside the square root:
f(g(x)) = √(6x^2 - 1)
So, the composite function f(g(x)) is given by:
f(g(x)) = √(6x^2 - 1)
for such more question on composite function
https://brainly.com/question/10687170
#SPJ3
HELP PLEASE!
simplify
(2x^3y)^3 / (4xy^2)^2(xy^3)
Answer:
[tex]\large\boxed{\dfrac{(2x^3y)^3}{(4xy^2)^2(xy^3)}=\dfrac{x^6}{2y^4}}[/tex]
Step-by-step explanation:
[tex]\dfrac{(2x^3y)^3}{(4xy^2)^2(xy^3)}\qquad\text{use}\ (ab)^n\ \text{and}\ (a^n)^m=a^{nm}\\\\=\dfrac{2^3(x^3)^3y^3}{4^2x^2(y^2)^2xy^3}\qquad\text{cancel}\ y^3\\\\=\dfrac{8x^{(3)(3)}y^3\!\!\!\!\!\diagup}{16x^2y^{(2)(2)}xy^3\!\!\!\!\!\diagup}\\\\=\dfrac{8\!\!\!\!\diagup^1x^9}{16\!\!\!\!\!\diagup_2x^2y^4x}\qquad\text{use}\ a^na^m=a^{n+m}\\\\=\dfrac{x^9}{2x^{2+1}y^4}\\\\=\dfrac{x^9}{2x^3y^4}\qquad\text{use}\ \dfrac{a^n}{a^m}=a^{n-m}\\\\=\dfrac{x^{9-3}}{2y^4}\\\\=\dfrac{x^6}{2y^4}[/tex]
What are the solutions of the equation x^4+ 95x^2-500=0? Use factoring to solve
Answer:
x^4+100x^2-5x^2-500=0
x^2(x^2+100)-5(x^2+100)=0
(x^2+100)(x^2-5)=0
from first expression
x^2+100=0
x^2=-100
x= root under -100
Therefore x=-10
from next expression
x^2-5=0
x^2=5
Or x=2.23
Step-by-step explanation:
Answer:
x = ± sqrt(5)
x = ±10i
Step-by-step explanation:
x^4+ 95x^2-500=0
What two numbers multiply to -500 and add to 95
-5 * 100 = -500
-5 +100 = 95
(x^2 - 5) (x^2 + 100) = 0
Using the zero product property
x^2 -5 =0 x^2 +100 =0
x^2 -5+5 =0 x^2 +100-100 = 0-100
x^2 =5 x^2 = -100
Take the square root of each side
x = ± sqrt(5) x = imaginary numbers
x = ±10i
Jeri is 3 years younger than Laura, whose age is x. How old is Jeri? x - 3 yrs old x + 3 yrs old 3x yrs old
Answer:
3x yrs old
Step-by-step explanation:
Which of these is a trinomial?
A. 2x-7
B. 2x2 - 7/3 + 14
c. 2y2 + 7y
D. 5xy
Answer:
the answer is D
Step-by-step explanation:
a is not it has a negative
a b is not it has an equation in it
so that leaves it to see and d c does not work
because it has to have two variables per one number
If X || Y and Y || Z then___
Answer:
X is parallel to Z
X || Z
Step-by-step explanation:
This is called the transitive property.
It says something like:
If f is related to g and g is related to h, then f is related to h.
The parallel relationship is transitive.
That is,
if X is parallel to Y and Y is parallel to Z, then X is parallel to Z.
NEED HELP ASAP PLEASE
Find the ratio of the known sides and calculate X.
1. The smaller triangle is half the size of the lager one:
6/12 = 1/2
10/12 = 1/2
This means x is half the length of 16
x = 16/2 = 8
2. 18/30 = 3/5
9/15 = 3/5
This means x is 3/5 of 25
x = 25 * 3/5 = 15
3. 32/24 = 1 1/3
16 /12 = 1 1/3
X is 1 1/3 times the length of 21
x = 21 x 1 1/3
x = 28
4. 12/15 = 4/5
20/25 = 4/5
x is 4/5 the length of 40
x = 40 * 4/5
x = 32
Choose the equation that represents the line that passes through the point (6,-3,) and has a slope of 1/2
Answer:
[tex]y=\frac{1}{2}x-6[/tex]
Step-by-step explanation:
The general equation of a line: [tex]y = ax+b[/tex]
In our case a is given
[tex]a=\frac{1}{2}[/tex]
Now we plug in for a and we get:
[tex]y=\frac{1}{2}*x+b[/tex]
Now we plug in our coordinates into this equation and we solve for b
[tex]-3=\frac{1}{2}*6+b\\b = -6[/tex]
So the equation of the line is [tex]y=\frac{1}{2}x-6[/tex]
Answer:
[tex]y=\frac{1}{2}x-6[/tex]
Step-by-step explanation:
Since the Inclination of the line was already given to us. Let us use Inclination of line formula:
[tex]m=\frac{y-y_0}{x-x_0}[/tex]
Plugging it in those values then we have the equation of the line:
[tex]\frac{1}{2}=\frac{y+3}{x-6}[/tex]
Rewriting, multiplying both sides
2y+6=x-6
2y=x-12 Rearranging
[tex]y=\frac{1}{2}x-6[/tex]
3Q + 4T = 26. P=2T=3Q l. What is 6P?
The answer is 52 but I don’t understand how they got this answer
Step-by-step explanation and answer:
The given equations P=2T=3Q can be split up into
P=2T..................(1)
P=3Q................(2)
since they are all equal.
Rewrite the given equation
3Q + 4T = 26 .............(3)
as
3Q + 2(2T) = 26 ...........(4)
and substitute (1) and (2) into (4)
P + 2(P) = 26 .................(5)
Multiply (5) by two to get
6P = 2*26 = 52 ..............(6)
as given.
Answer:
see explanation
Step-by-step explanation:
Given P = 2T = 3Q, then
3Q + 4T = 26 can be expressed as
P + 2P = 26
3P = 26 ( multiply both sides by 2 )
6P = 52 ← as required
What is the volume of the regular pyramid bellow?
Answer:
128 units^3
Step-by-step explanation:
[tex]v = \frac{b \times b \times h}{3} = \\ = \frac{8 \times 8 \times 6}{3} = \\ = 128 \: {units}^{3} [/tex]
Step-by-step explanation:
base areas x height / 3
a^2 . h / 3
8^2 . 6 / 3
= 128 units^3
iyi ödevler
have a good lesson
IXL/HELP!!
What is the answer
Answer:
20.6
Step-by-step explanation:
28.6×20.6=589.16
Answer:
20.6
Step-by-step explanation:
Area of a rectangle = base times height
A = bh
Substitute in what we know
589.16 = 28.6 * h
Divide each side by 28.6
589.16/28.6 = 28.6h/28.6
20.6=h
Ella is stuffing envelopes. She has 48 red pages, 25 white pages, and 84 blue pages. If she need to put 2 red pages, 1 white pages, and 4 blue pages in every envelope to make it complete, how many complete envelopes can she make?
Ella can make 21 complete envelopes with her available red, white, and blue pages, since the number of complete sets is limited by the blue pages.
Ella has 48 red pages, 25 white pages, and 84 blue pages. She needs to put 2 red pages, 1 white page, and 4 blue pages in every envelope. To find out how many complete envelopes she can make, we need to calculate the number of complete sets of pages she can create based on the quantity of each color she has and the number she needs for each envelope.
For the red pages: 48 red pages / 2 pages per envelope = 24 envelopes
For the white pages: 25 white pages / 1 page per envelope = 25 envelopes
For the blue pages: 84 blue pages / 4 pages per envelope = 21 envelopes
Since the number of envelopes is limited by the color with the least amount of complete sets, Ella can make 21 complete envelopes because she will run out of blue pages after the 21st envelope.